R&D investment, IPO underpricing, investor sentiment and long-term performance: A study on the Chinese star market - Li, Menghan; Zhao, Fengyu (Asian Development Policy Review, 2025)
This study examines the factors influencing sustained post-IPO performance in China’s STAR Market, emphasizing the combined effects of R&D expenditure, IPO underpricing, and investor sentiment on long-term outcomes in this innovation-driven exchange. Using event study analysis and multiple regression, the research evaluates 342 companies listed between July 2019 and December 2021. Long-term performance is measured via one-year cumulative abnormal returns (CAR) and buy-and-hold abnormal returns (BHAR). R&D expenditure significantly enhances long-term performance for non-high-tech firms by signaling growth potential in environments with limited information. High-tech firms, however, show minimal incremental gains, as market expectations pre-price their innovative status. IPO underpricing consistently correlates negatively with long-term performance across sectors, indicating agency costs or adverse signaling. Investor sentiment, proxied by initial trading turnover, exerts negligible lasting impact, revealing a disconnect between speculative activity and sustained valuation. Sector-specific R&D signaling and IPO underpricing risks drive long-term outcomes. Market expectations dominate pre-IPO valuations for high-tech firms, while short-term speculation fails to predict enduring performance. Firms should align R&D strategies with sector-specific valuation drivers. Investors must prioritize fundamentals over transient hype. Policymakers can enhance market efficiency by fostering transparency and incentivizing innovation, particularly in non-high-tech sectors, to support sustainable growth in emerging markets.